The effect of pole length on physiological and perceptual responses during G3 roller ski skating on uphill terrain - Torvik, Per-Øyvind; Heimburg, Erna Dianne von; Sende, Torkel; Welde, Boye (PloS one, 2019)
The benefits of using longer than self-selected poles have been shown in double poling, but these potential benefits have not been examined in the gear 3 ski skating sub-technique (G3), during which the poling movement is very similar to double poling. The aim of this study was to examine the effect of longer than self-selected poles on physiological and perceptual responses in the G3 sub-technique. Ten cross-country skiers and biathletes (VO2max 72.4 ± 3.0 ml∙min-1∙kg-1, age 20.1 ± 2.8 years, height 1.81 ± 0.03 m and weight 73.1 ± 4.6 kg) completed two tests, each with three different submaximal intensities, during roller skiing using the G3 technique. The first test was carried out at a fixed speed (10 km∙h-1) and the skiers performed two intervals of 5 min at 7, 9 and 11% inclination on a roller ski treadmill with self-selected poles (SSP) and 7.5 cm longer poles (LP) at each step. The second test had a fixed inclination of 4% and speeds of 14, 17 and 20 km∙h-1, also performed with SSP and LP at each step. At fixed speed, the oxygen uptake was 2.7% lower (P = 0.005) and the gross efficiency (GE) 2.1% higher (P = 0.01) with LP than with SSP at the steepest inclination of 11%. At fixed inclination, the oxygen uptake was 2.1% lower (P = 0.01) and the GE was 4.1% higher (P = 0.03) with LP than with SSP at the highest speed of 20 km∙h-1. At 14 km∙h-1, the oxygen uptake was 3.0% lower (P = 0.05) and GE was 3.8% higher (P = 0.03) with LP than with SSP. Our novel findings show that longer poles in the G3 technique may enhance the efficiency of skiing.